(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The aim of the study is to investigate the effect of flipped classroom learning strategy on students’ academic achievement in Basic Technology in junior secondary school in Rivers State. Two research questions were posed to guide the study. Two null hypotheses was formulated and tested at .05 level of significance. The study adopted a quasi-experiment design. The population for the study consisted of only government Junior Secondary School two (JSS 2) Basic Technology students in the 14 (fourteen) public secondary schools in Obio/Akpor local government area of Rivers State. A total of six thousand, one hundred and twenty-seven (6,127) JSS 2 students comprising; three thousand, seven hundred and Ninety-nine (3,799) male and two thousand three hundred and twenty-eight (2,328) female. One hundred and fifty (150) junior secondary school two (JSS 2) Basic Technology students in three intact classes constituted the sample size for the study. The instrument for data collection was Basic Technology Achievement Test (BTAT) which consists of 30 multiple choice questions developed by the researcher to assess students’ achievement in the experimental and control groups respectively. The research instrument were subjected to face and content validity by three (3) experts. Thereafter the reliability of the instruments was determined using test-re-test method. The initial and re-test scores of the sample were correlated and computed using Pearson’s Product Moment Correlation Co-efficient to obtain the reliability index of 0.80. The data obtained from the study was analyzed using mean statistics and standard deviation which answered the research questions while Analysis of covariance (ANCOVA) at .05 level of significance was used to test the null hypotheses. The findings of the study revealed that Students taught with flipped classroom performed better than those taught with traditional learning method. In addition, flipped classroom enhanced the achievement of both male and female for both male and female students than the traditional learning method. The researcher recommended that Basic Technology teachers should be encouraged to adopt blended learning approach especially flipped classroom strategy because it will help to improve students’ academic performance. Students should be encouraged to study together irrespective of their gender to eliminate gender biases.